A Toll‐like receptor 2 genetic variant modulates occurrence of bacterial infections in patients with sickle cell disease. (25th March 2019) - Tozatto‐Maio, Karina; Girot, Robert; Ly, Indou D.; Rocha, Vanderson; Silva Pinto, Ana C.; Diagne, Ibrahima; Benzerara, Yahia; Dinardo, Carla L.; Kashima, Simone; Leston‐Araujo, Itauá; Kenzey, Chantal; Fonseca, Guilherme H. H.; et al.
Summary: Despite adequate immunization and penicillin prophylaxis, bacterial infections remain a leading cause of morbidity and mortality in patients with sickle cell disease (SCD). Besides hyposplenism, inflammatory and genetic factors might modulate their susceptibility to bacterial infections. We performed a candidate gene association of single nucleotide polymorphisms (SNPs) located in Toll‐like receptor ( TLR ) genes, encoding prominent molecules for innate immune responses, with the occurrence of bacterial infections in patients with SCD. A cohort followed in centres in Brazil, France and Senegal ( n  = 430) was divided in two groups: patients who presented at least one episode of bacterial infection ( n  = 235) and patients who never had bacterial infections ( n  = 195). There were no differences in gender or age distribution among the groups. The frequency of the TLR2 rs4696480 TA genotype was significantly lower in the infected group (50% vs. 67%, odds ratio [OR] = 0·50, 95% confidence interval [CI] 0·34–0·75, P  < 0·001), and the TT genotype was significantly higher in the infected group (15% vs. 5%, OR = 3·18, 95% CI 1·53–6·61, P  < 0·001). Previous reports demonstrated higher secretion of inflammatory factors in cells from AA individuals, lower occurrence and severity of immune diseases in T carriers. The rs4696480 TA genotype might stand between deleterious effects of over inflammatory response (AA genotype) and inefficient responses ( TT genotype) to infectious agents in SCD settings.